Pendampingan Asuhan Keperawatan Medikal Bedah pada Klien dengan Gangguan Sistem Pencernaan: Gastroenteritis Akut - Suhanda; Nizar Ahmad (Yayasan Inspirasi El Burhani, 2022)
Introduction: Acute gastroenteritis is a disease that occurs when there is a change in the consistency of the stool apart from the frequency of bowel movements. Gastroenteritis is caused by a viral infection. There are two types of viruses that are the main causes of gastroenteritis, namely Norovirus and Rotavirus. In addition to these two types of viruses, gastroenteritis can also be caused by Adenovirus and Astrovirus. Objective: The purpose of this case study is to identify and implement nursing care for patients with acute gastroenteritis in the Melati Room, 3rd floor of RSUD dr. Soekarjo, City of Tasikmalaya. Method: Nursing assessment is a process carried out by nursing staff to patients continuously to collect information or data in determining nursing problems experienced by patients. Nursing diagnoses are clinical assessments of individual, family, or community responses to actual or potential health problems/life processes. Nursing intervention is a guide for the specific behavior expected of the client, and/or actions that must be taken by the nurse. Nursing implementation is a category of a series of nurse behaviors that coordinate with patients, families, and other members of the health team to assist patients' health problems in accordance with predetermined planning and outcome criteria. Evaluation is an attempt to measure and evaluate objectively the achievement of the results that have been previously planned. Result: The results of the case study on the patient Mr. H with acute gastroenteritis found one nursing problem, namely fluid volume deficit related to active fluid loss. The interventions specified are monitoring hydration status, mucosal moisture, adequate pulse, orthostatic blood pressure, monitoring vital signs, recording accurate intake and output and collaborative intravenous fluid administration. Conclusion: This nursing care assistance has obtained the necessary data for nursing intervention plans. After nursing diagnoses are established, nursing interventions are implemented and evaluated.